RECENT SATELLITE OBSERVATIONS AT SYOWA STATION, ANTARCTICA - ワラシナ, ヒデオ; エノモト, ヒロユキ; WARASHINA, Hideo; ENOMOTO, Hiroyuki (National Institute of Polar Research, 1995)
P(論文) Various data from satellites have been received since 1989 at Syowa Station, Antarctica by the Multi Purpose Satellite Data Receiving System. This receiving system expands the observation area. SAR (Synthetic Aperture Radar) data obtained since 1991 are very important for research on environmental change on the global scale. The frequency of use of the receiving system has recently increased. Data from five satellites were received during the wintering of the 34th Japanese Antarctic Research Expedition. This system has about 1700 reception paths. The number of paths will increase because there is a plan for launches of new satellites such as the Earth Observation Satellite. Recently, troubles with the receiving system have increased suddenly. It has been found that the increase in receiving paths has partly caused the trouble due to the tight schedule. We should organize efficient receiving plans for effective use of this system. Plans for efficient obsevation in the future include. 1) Doubled hardware and strengthening of the backup system, including international support. 2) Planning of long range observations. 3) Establishment of a data center or information center for various users including international committees and also individual researchers. departmental bulletin paper